Fixing Flexner: Disrupting and Rebuilding Academic Medicine for Women of Color to Lead - Chelsea Dorsey; Vineet M Arora; Keme Carter (Journal of Medical Internet Research, 2023)
In an effort to address the lack of compositional diversity seen in academic leadership, our generation has an opportunity to rebuild academic medicine in a way that welcomes, values, and supports the development and success of women of color.